Analysis Of Agricultural Sector Growth And Inflation On Farmer Exchange Rate In Indonesia - Ayub Hasan; Sri Indriyani Dai; Ivan Rahmat Santoso; Syarwani Canon (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study analyzes the effect of agricultural sector growth and inflation on farmer exchange rates in Indonesia. The data used in this research is secondary data and sourced from the Central Bureau of Statistics obtained from 34 provinces in Indonesia. This study uses multiple linear regression Analysis of panel data using the Fixed Effect Model (FEM). The results of this study indicate that: (1) the growth of the agricultural sector has a positive and significant effect on farmer exchange rates, meaning that every one percent increase in agricultural sector growth can increase farmer exchange rates in Indonesia; (2) Agricultural sector inflation has a positive and significant effect on farmer exchange rates, meaning that every one percent increase in agricultural sector inflation can increase farmer exchange rates in Indonesia.